HYDROELECTRIC PLANTS AND CONSERVATION UNIT IN THE AMAZON - Cavalcante, Maria Madalena Aguiar; Costa, Gean Magalhães; Silva, Girlany Valéria Lima; Moret, Artur Souza (Mercator, 2021)
The expansion of hydroelectric plants (HEPs) in the Brazilian Amazon region attracts attention because of its several social, economic, and ecological impacts, and because its directly or indirectly affects institutional areas in charge of protecting biodiversity and traditional populations. Among the thirteen interlinked sub-basins of the Amazon river (on the Brazilian border), there are nine hydroelectric plants in operation and an additional seventy five (75) are planned for construction, of which 60 per cent will be built in the Tapajos river basin. The objective of the article is to expose the economic appropriation of this basin, and the social and environmental expropriation taking place in the region. The analysis of these processes requires the spatial mapping of the existing and planned hydroelectric plants and areas officially protected, by hydrological basins. The result points at the confrontation between the developmentalist policies related to the construction of HEPs in the Amazon region and the environmental policies oriented, especially, to protected areas, which shows the social and environmental expropriation happening in this basin. Keywords : Amazonia, Hydroelectric Plants, Conservation Units, Watersheds.